The Intertemporal Spending Behavior of Local Governments: A Comparative Analysis of the Scandinavian Countries - Lars-Erik Borge; Matz Dahlberg; Per Tovmo (Uppsala University, Department of Economics, 2001)
The paper investigates the intertemporal spending behavior of Scandinavian local governments with particular attention to liquidity constraints imposed by balanced-budget-rules and other regulations. The main finding is that Danish local governments are more able to smooth current expenditures than their Norwegian and Swedish counterparts. Whereas the permanent-income hypothesis cannot be rejected for Denmark, it is in most cases rejected for Norway and Sweden. The Swedish system of market-based control and the Norwegian system of administrative control seem to produce similar results in terms of consumption smoothing.
urn:nbn:se:uu:diva-2518
Keywords: D99; H72; 330; Local government consumption; Intertemporal decision-making; Kommunale Ausgaben; Vergleich; Schweden; Norwegen; Dänemark